A Comparative Study on Reporting Verbs in ELT Research Article Introductions by Indonesian Authors - Ibesti Agenum Raningrum; Safnil Arsyad; Muhammad Fadhli (UNIB Press, 2022)
The study of reporting verbs (RVs) is rarely done by Indonesian scholars. Therefore, this research aimed to investigate how Indonesian writers used the RVs in research article introductions published in low-ranking and medium-ranking ELT journals and investigating the differences of the usage of RVs used by them in both groups of journals. This research used a quantitative approach with a comparative design that investigated 40 research article introductions published in low-ranking (SINTA 6: Journal of English Language Education, and SINTA 5: The Journal of English Literacy Education) medium-ranking (SINTA 4: Journal of English Education and Teaching, and SINTA 3: ELT Forum: Journal of English Language Teaching) ELT journals in 2021. The data were taken by using the purposive sampling technique and they were analyzed by using the RVs’ framework of Francis et al. (1996). The results revealed that Indonesian writers of low-ranking and medium-ranking ELT journals used all of the RVs in research article introductions, but the most frequent RVs used by them was “argue verb”. Moreover, Indonesian writers of low-ranking ELT journals used more “find and think verbs”. Meanwhile, “the argue and show verbs” were more often used by Indonesian writers of medium-ranking ELT journals. These findings indicate the importance of using the RVs in writing the research article introductions for Indonesian writers in the field of English language teaching. The writers are suggested to use more “Argue Verbs, followed by “Find and Shows Verbs” when writing research article introductions. Keywords: ELT journals, research article introduction, low-ranking journal, medium journal, reporting verb